Flexible link aerator for dissolved oxygen generation in tiger prawn pond - Mat Shah, Muhammad Amir (2014)
In the aquaculture industry, the dissolved oxygen is one of the important parameters that need to be monitored seriously. Aerator is normally used to increase the level of dissolved oxygen in water. It functions to circulate or mixes the water top to bottom to ensure that the oxygen content is uniform throughout the pond. It also exposes the water surface to absorb oxygen from atmosphere. This aerator uses a new concept by using flexible link to generate dissolved oxygen. The advantages that have in flexible link were used as an actuator to generate and distribute dissolved oxygen in water. Three type experiments were done to find out and verified the optimum parameter setting for this aerator. The best result of dissolved oxygen level were found during run the flexible link aerator at full power with 0.65m length of flexible link and immerses 25% in water. As a result, the flexible link was successfully implemented as a new aerator concept where it is able to generate oxygen up to 8.6mg/L with the average Standard Oxygen Transfer Efficiency 1.84 kgO2/kWhr and suitable to used in the shallow pond. The key success factor in developing this method is due to the characteristics that are available on flexible link where it length can be extended to cover the surface of the water without burdening the motor. More water surface area exposed to the atmosphere it will encourage the absorption oxygen into water.